Perspektif Mahasiswa Fakultas Psikologi Angkatan 2015 Universitas Yarsi Jakarta Pusat Terhadap Aplikasi Chemical Castration (Kebiri) Bagi Pelaku Kekerasan Seksual Anak Di Indonesia Dan Tinjauannya Menurut Islam - Nisrina Nurul Insani; Bambang Poerwantoro; Zuhroni Zuhroni (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2018)
The criminal behavior of sexual violence has a fairly high level of quantity in Indonesia, and not infrequently victims of this type of crime are children of underage. in May 2016, President Joko Widodo has signed a law enforcement regulation (Perppu) number 1 of 2016 on the second change number 23 of 2002 on child protection. In the perppu described, perpetrators of sexual crimes against children, can be threatened with the death penalty. Meanwhile, the use of chemical substances and the installation of electronic detection equipment can also be considered by the judge to provide additional punishment. This study aims to determine the perspective of students faculty of psychology class of 2015 Yarsi University central Jakarta to the application of chemical castration (kebiri) for child sex offenders in Indonesia and its review according to Islam. Research method used descriptive with cross sectional approach. Sampling technique in this research is purposive sampling. The result showed 32 respondents, 18 respondents (56.3%) did not agree and 14 students (43.7%) agreed. Student perspective of the faculty of psychology class of 2015 Yarsi University Central Jakarta does not agree to the application of chemical castration (kebiri) for child sexual violence perpetrators in Indonesia. According to Islam's view, the enactment of chemical curiosity as punishment for perpetrators of sexual violence is forbidden because it includes human torture and bodily harm.